Formation Of Methodological Components For Solving NonStandard Problems In Mathematics (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Below in this article, an opinion is expressed about the necessary, targeted introduction of methodological innovations aimed at solving non-standard problems on the topic of mathematics “Pythagorean Theorem” among students of general secondary education, special and presidential schools.